Kemajuan Teknologi Informasi Dan Telekomunikasi Terhadap Perkembangan Tindak Pidana Cyber Crime - Simanjuntak, Dahlan; Sudarto, Sudarto; Sujono, Sujono (LITERATUS, 2025)
The advancement of information technology provides many conveniences for human life, but this advancement also simultaneously gives rise to various problems that are not easy to find a way out of. One of the problems that arises due to the development of information technology is the birth of crimes that are "new" in nature, especially those that use the internet as a tool. Lazaim is known as cyber crime. The research method used is normative juridical. The results of the study are the Influence of advances in information and telecommunications technology on the development of cyber crime that in the advancement of cyber crime technology, dozens of types of cyber crimes occur. Meanwhile, those included in the category of general crimes facilitated by technology include credit card fraud, stock exchange fraud, banking fraud, child pornography, drug trafficking, and terrorism. While crimes that use information technology are defacing, cracking, or phreaking. Currently, the existence of the ITE Law is absolutely necessary for the State of Indonesia, because currently Indonesia is one of the countries that has used and utilized technology widely and efficiently, but does not yet have a Cyber Law. In the view of responsive law which is an approach that adapts to the needs of society and the development of the times. Legal policy in overcoming the influence of technology on the development of cyber crime is divided into penal and non-penal means. Cyber crime is a major challenge in the digital era, but also an opportunity to develop a more responsive and progressive legal system. In the view of progressive law, handling cyber crime must be oriented towards substantive justice, flexibility, and humanization of law.